2017
DOI: 10.1177/0032321716674024
|View full text |Cite
|
Sign up to set email alerts
|

Neither Repression Nor Concession? A Regime’s Attrition against Mass Protests

Abstract: Protest activists employ various strategies to challenge regimes, and regimes deploy multifaceted tactics to respond to such challenges. Existing studies on regime protest responses focus on repression and concession, but little attention is devoted to toleration, which is often regarded as government inaction. Drawing on primary sources and interviews, this article analyses regime responses to Hong Kong’s Umbrella Movement to expand the conceptualisation of toleration. First, it demonstrates that regimes adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 48 publications
(44 reference statements)
1
33
0
Order By: Relevance
“…The existing literature has identified that the law can be used to control social movements, but there has been little discussion of the factors that influence protesters to obey the law when facing legal instruments. Whether the country or region has an established rule of law is certainly important to understanding whether protesters will comply with the law (Barkan 1984;Yuen and Cheng 2017). This article adds to the literature by also arguing that it is important to understand how protesters interpret the movement through their collective action frame.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The existing literature has identified that the law can be used to control social movements, but there has been little discussion of the factors that influence protesters to obey the law when facing legal instruments. Whether the country or region has an established rule of law is certainly important to understanding whether protesters will comply with the law (Barkan 1984;Yuen and Cheng 2017). This article adds to the literature by also arguing that it is important to understand how protesters interpret the movement through their collective action frame.…”
Section: Resultsmentioning
confidence: 96%
“…The repression by the government and other social actors vis-à-vis the Occupy Movement has been another subject of study. Yuen and Cheng (2017) note that the government responded to the movement through a strategy of attrition: while seemingly tolerating the street occupation, the government made attempts to maintain elite cohesion, mobilize counter-movements, and leverage legal instruments. Some attackers from the counter-movements were low-level triads (organized crime syndicates operating in Hong Kong) (Varese and Wong 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A coalition known as the Alliance for Peace and Democracy was also established in July 2014, comprising more than 1,500 pro-Beijing political parties, industry associations, and mass organisation, to rally against Occupy Central. Together, these pro-regime forces played a crucial role in creating chaos in the protest camp and thereby constraining leaders' strategic moves, which enervated the 79-day Umbrella Movement (Yuen and Cheng 2017).…”
Section: Social Measures: Countermovementsmentioning
confidence: 99%